Implementasi Nilai-Nilai Pendidikan Pada Tradisi Perlombaan Main Jaran (Pacuan Kuda) Di Desa Penyaring Kabupaten Sumbawa - Kurniawati, Luthfiyah; Utama, Abdul Alimun; Junaidi, Junaidi (Jurnal Ilmiah Mandala Education (JIME), 2022)
This study aims to describe how to implement educational values in the tradition of playing jaran (horse racing) in Penyaring Village, Sumbawadan Regency to describe the supporting and inhibiting factors of educational values in the tradition of playing jaran (horse racing) in Penyaring Village, Sumbawa Regency. This type of research uses a qualitative approach. The data collection techniques used are: observation, interviews and documentation. The data analysis technique in this study used descriptive analysis by analyzing all interview transcripts and matching them with observational notes. The purpose of this study is to describe how to implement educational values in the tradition of the main jaran (horse racing) race in Penyaring Village, Sumbawa Regency and to describe the supporting and inhibiting factors of educational values in the tradition of the main jaran race (horse racing) in Penyaring Village Kabupa... This research is also expected to be used as a reference. Meanwhile, the Urgency of this research is expected to provide general guidance on the implementation of educational values in the tradition of playing jaran (horse racing) in Penyaring Village, Sumbawa Regency.